Penggunaan LMS Berbasis Mobile Menggunakan Design Thinking pada Mata Kuliah Pancasila - Ambiro Puji Asmaroini (Universitas Muhammadiyah Ponorogo, 2023)
The purpose of this research is to find learning innovations in the use of mobile-based LMS in the Pancasila course. The LMS used is bebas.umpo.ac.id. Methods in research using design thinking. The processes in design thinking are empathizing, defining, ideating, prototyping, and testing. The process includes contextual analysis, problem finding and framing, generating ideas and solutions, creative thinking, sketches and drawings, modeling and prototyping, testing, and evaluation. The results of the study show that the use of a mobile-based LMS makes it easier for students to take part in online learning which can be accessed via bebas.umpo.ac.id.